Progress of Cooperative Banks in India - K. Nagi Reddy; Dr. M. Chandraiah (International Journal of Engineering and Management Research, 2019)
Cooperative is one of the oldest and effective systems in terms of development of human civilization. Cooperative institutions are organized and managed on the principle of cooperation, self-help and mutual help. There are different types of cooperative institutions functioning in India. As far as the institutional credit structure is concerned, cooperatives play a significant role in this regard. Cooperative credit institutions are spread all over India and are providing their services at the grass root level. As main portion of the population in India lives in rural areas so it is important to strengthen the cooperative credit institutions in these areas. The major advantage of the institutions is their strong branch network which covers entire area of the country. This paper attempts to study the Co-operative Banking in India. The paper mainly focuses on the branch networking, capital, advances, deposits, borrowing, loans issued and outstanding performance of these banks in India. Basically we have studied the growth and performance of Co-operative Banks in India. The study is based on secondary data. The data required for the study has been collected from RBI annual reports, Journals, reports on trend and progress of banking in India, Annual Reports of NAFSCOB etc.